EXPERIENCE OF FOREIGN COUNTRIES IN THE INTRODUCTION OF DIGITAL TECHNOLOGIES INTO THE FINANCIAL SYSTEM - Xusanova Dilorom Shavkatovna (Scholars Digest Publishing, 2024)
In recognition of the growing problems of competition in the context of globalization, innovation is essential for the feasibility and richness of the economy. In this regard, innovation in developed countries is the main pillar of the country's economic development, and it is being viewed as one of the most important issues of government policy. This article analyzes the ways of introducing digital technologies in the financial system, as well as issues related to the experience of developed countries in this regard.